Labor movement : how migration regulates labor markets - Bauder, Harald, 1969- (Oxford University Press, 2006)
Drawing on Pierre Bourdieu and other prominent thinkers, this book presents case studies in Europe and North America. It unravels the web of regulatory labor market processes related to international migration and illustrates how social distinction, cultural judgement, and citizenship subordinate international and foreign workers.